The Relationship Between PSN Behavior with Existence Larvae of Aedes aegypti In Port of Pulang Pisau - Nani Nani (Universitas Airlangga, 2017)
The existence of Aedes aegypti larvae is an indicator of the existence of Aedes aegypti mosquito populations in the area. This mosquito is a vektor that can transmit diseases like Dengue, Zika, Yellow Fever and Chikungunya. The most effective efforts to eradicate mosquito larvae are within off the circle of mosquito chain that is by conducting mosquito nest eradication (PSN). Factors that may affect the existence of Aedes aegypti larvae are PSN behavior that consist of knowledge, attitudes and practice. The purpose of this study was to analyze the relationship of knowledge, attitudes and practice mosquito eradication with existence of Aedes aegypti larvae. This study use cross sectional design with a sample size of 80 respondents selected by simple random sampling. To determine the relationship between the dependent variable and independent variables used chi square test. The independent variable in this study is the knowledge, attitude and practice. The results of this study show that based on the chi square test with α = 5% knowledge (p value = 0,004; PR = 1,76; CI 95% 1,19-2,59), attitude (p value = 0,024 ; PR = 1,55 ; CI 95% 1,08-2,24) and the PSN practice (p value = 0,000, PR = 3,89; CI 95% 2,01-7,52) relationship with existence larvae. The conclusion is that there are relationship between knowledge, attitude and practice PSN with the exixtence of Aedes aegypti larvae in the Port of Pulang Pisau. Keywords: the existence of larvae of Aedes aegypti, knowledge, attitudes, practice PSN